Effect of Si+ ion implantation in α-Ga2O3 films on their gas sensitivity - Yakovlev, Nikita N.; Almaev, Aleksei V.; Butenko, Pavel N.; Tetelbaum, David; Mikhaylov, Alexey; Nikolskaya, Alena; Pechnikov, Aleksei I.; Stepanov, Sergey I.; Boiko, Mikhail; Chikiryaka, Andrei V.; Nikolaev, Vladimir I. (IEEE sensors journal)
The effect of the Si+ ion implantation on the gas-sensing properties of single-crystal (0001) α-Ga2O3 films grown by halide vapor phase epitaxy (HVPE) has been studied. It is established that irradiation with a dose of 8 × 1012– 8 × 1015 cm−2 at an energy of 100 keV followed by postimplantation annealing increases the response of α-Ga2O3 films to 3 vol% of H2 by 43 times at 400 ◦C, reduces the response time by a factor of 6, and expands the operating temperature range down to 30 ◦C. In addition, α-Ga2O3 layers irradiated with a Si+ ion dose of 8 × 1013–8 × 1015 cm−2 demonstrate high sensitivity to CO and NH3 gases. The mechanism of Si+ ion irradiationeffect on the gas-sensingproperties of α-Ga2O3 structures is proposed.